Eigenvalue assignment in fractional descriptor discrete-time linear systems - Kaczorek, Tadeusz; Borawski, Kamil (Archives of Control Sciences, 2017)
Abstract The problem of eigenvalue assignment in fractional descriptor discrete-time linear systems is considered. Necessary and sufficient conditions for the existence of a solution to the problem are established. A procedure for computation of the gain matrices is given and illustrated by a numerical example.